INTEGRATION OF PHILOSOPHY OF SCIENCE IN THE DEVELOPMENT OF A HOLISTIC COUNSELING MODEL - Yuttami Keila Azahra; Patima Aprilia Azzahra; Zakia Amalia Putri (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study examines the integration of philosophy of science in the development of a holistic counseling model through a literature review of ten relevant articles. The results of the study show that philosophy of science plays a fundamental role through three integrated dimensions: ontology, which views humans as complex beings with biological, psychological, social, and spiritual dimensions; epistemology, which integrates the paradigms of postpositivism, constructivism-interpretivism, and critical-ideological; and axiology, which emphasizes professional ethical values. The integration of these three dimensions enables counseling practices to be more meaningful, effective, and responsive to the complexity of contemporary issues. The main challenge faced is the gap in philosophical understanding among counseling practitioners. A holistic counseling model based on the integration of the philosophy of science is a theoretical and practical necessity for producing comprehensive counseling services that are appropriate to the Indonesian socio-cultural context.